Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Shifts in Ecological Legacies Support Hysteresis of Stand Type Conversions in Boreal Forests - X. J. Walker; K. Okano; L. T. Berner; R. Massey; S. J. Goetz; J. F. Johnstone; M. C. Mack (Ecosystems, 2023)

Distinct patterns of inheritance shape life‐history traits in steelhead trout - Anne K. Beulke; Alicia Abadía‐Cardoso; Devon E. Pearse; Laura C. Goetz; Neil F. Thompson; Eric C. Anderson; John Carlos Garza (Molecular Ecology, 2023)
Life‐history variation is the raw material of adaptation, and understanding its genetic and environmental underpinnings is key to designing effective conservation strategies. We used large‐scale genetic pedigree reconstruction of anadromous steelhead trout ( Oncorhynchus mykiss ) from the Russian River, CA, USA, to elucidate sex‐specific patterns of life‐history traits and their heritability. SNP data from adults returning from sea over a 14‐year period were used to identify 13,474 parent–offspring trios. These pedigrees were used to determine age structure, size distributions and family sizes for these fish, as well as to estimate the heritability of two key life‐history traits, spawn date and age at maturity (first reproduction). Spawn date was highly heritable ( h 2 = 0.73) and had a cross‐sex genetic correlation near unity. We provide the first estimate of heritability for age at maturity in ocean‐going fish from this species and found it to be highly heritable ( h 2 from 0.29 to 0.62, depending on sex and method), with a much lower genetic correlation across sexes. We also evaluated genotypes at a migration‐associated inversion polymorphism and found sex‐specific correlations with age at maturity. The significant heritability of these two key reproductive traits in these imperiled fish, and their patterns of inheritance in the two sexes, is consistent with predictions of both natural and sexually antagonistic selection (sexes experience opposing selection pressures). This emphasizes the importance of anthropogenic factors, including hatchery practices and ecosystem modifications, in shaping the fitness of this species, thus providing important guidance for management and conservation efforts.

Modeling the impacts of a changing and disturbed environment on an endangered beluga whale population - Elizabeth A. McHuron; Manuel Castellote; Gina K. Himes Boor; Kim E.W. Shelden; Amanda J. Warlick; Tamara L. McGuire; Paul R. Wade; Kimberly T. Goetz (Ecological Modelling, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Crary bank: a deep foraging habitat for emperor penguins in the western Ross Sea - G. L. Kooyman; K. Goetz; C. L. Williams; P. J. Ponganis; K. Sato; S. Eckert; M. Horning; P. T. Thorson; R. P. Van Dam (Polar Biology, 2020)

Testing for hybridisation of the Critically Endangered Iguana delicatissima on Anguilla to inform conservation efforts - Kieran C. Pounder; F. Mukhida; R. P. Brown; D. Carter; J. C. Daltry; T. Fleming; M. Goetz; L. G. Halsey; G. Hughes; K. Questel; I. J. Saccheri; R. Williams; et al. (Conservation Genetics, 2020)
The Caribbean Island of Anguilla in the north-eastern Lesser Antilles is home to one of the last populations of the Critically Endangered Lesser Antillean iguana Iguana delicatissima . This population is highly threatened primarily because of hybridisation with non-native Iguana iguana . This study assesses the degree of hybridisation between Anguilla’s Iguana species firstly using morphological characteristics and then genetic analysis to validate the genetic integrity of morphologically identified I. delicatissima . We also examined the genetic diversity of Anguilla’s I. delicatissima population, and that of a population on the nearby island of Îlet Fourchue, St Barthélemy. Forty-five iguanas were captured in Anguilla and 10 in St Barthélemy, and sequences from 3 nuclear and 1 mtDNA genes were obtained for each. Of the 45 iguanas captured in Anguilla, 22 were morphologically identified as I. delicatissima , 12 as I. iguana and the remainder were identified as hybrids. Morphological assignments were all confirmed by genetic analyses except for one I. iguana and one hybrid individual. These two individuals appeared likely to have originated following ancestral hybridisation events several generations ago. A significant paucity of genetic diversity was found within Anguillan and St Barthélemy I. delicatissima populations, with a single haplotype being identified for each of the three nuclear genes and the mtDNA sequence. This study highlights the urgency for immediate action to conserve Anguilla’s remnant I. delicatissima population. Protection from hybridisation will require translocation to I. iguana -free offshore cays, with supplementary individuals being sourced from neighbouring islands to enhance the genetic diversity of the population.

A Southern Ocean archipelago enhances feeding opportunities for a krill predator - Lisa‐Marie K. Harrison; Kimberly Goetz; Martin J. Cox; Robert Harcourt (Marine Mammal Science, 2020)
Productivity in the oceans is heightened around oceanographic and bathymetric features such as fronts and islands. This can have a flow‐on effect, providing increased food availability for higher trophic level species. Using data from a 5‐day combined visual and acoustic survey, we examined the hypothesis that higher Antarctic krill ( Euphausia superba ) density provides a lucrative resource for humpback whales ( Megaptera novaeangliae ) at a remote Antarctic feeding area, the Balleny Islands (67 o S, 164°E). We assessed whale presence at the feeding area in relation to prey (krill), productivity and environmental variables using density surface modeling. We found stark differences between krill swarms near the islands and those in adjacent open water. Swarms were twice as dense and three times more numerous near the Balleny Islands compared to an open water pelagic environment, suggesting that the islands offered a profitable feeding opportunity. At the feeding area, whales were found in deeper and more productive waters with medium krill densities. These relationships, along with the high krill availability around the islands, may be the result of the Island Mass Effect.

Spatiotemporal remote sensing of ecosystem change and causation across Alaska - Neal J. Pastick; M. Torre Jorgenson; Scott J. Goetz; Benjamin M. Jones; Bruce K. Wylie; Burke J. Minsley; Hélène Genet; Joseph F. Knight; David K. Swanson; Janet C. Jorgenson (Global Change Biology, 2019)
Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio‐environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high‐latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using expert knowledge, remote sensing data, and spatiotemporal analyses and modeling. Time‐series analysis of moderate—and high‐resolution imagery was used to characterize land‐ and water‐surface dynamics across Alaska. Some 430,000 interpretations of ecological and geomorphological change were made using historical air photos and satellite imagery, and corroborate land‐surface greening, browning, and wetness/moisture trend parameters derived from peak‐growing season Landsat imagery acquired from 1984 to 2015. The time series of change metrics, together with climatic data and maps of landscape characteristics, were incorporated into a modeling framework for mapping and understanding of drivers of change throughout Alaska. According to our analysis, approximately 13% (~174,000 ± 8700 km 2 ) of Alaska has experienced directional change in the last 32 years (±95% confidence intervals). At the ecoregions level, substantial increases in remotely sensed vegetation productivity were most pronounced in western and northern foothills of Alaska, which is explained by vegetation growth associated with increasing air temperatures. Significant browning trends were largely the result of recent wildfires in interior Alaska, but browning trends are also driven by increases in evaporative demand and surface‐water gains that have predominately occurred over warming permafrost landscapes. Increased rates of photosynthetic activity are associated with stabilization and recovery processes following wildfire, timber harvesting, insect damage, thermokarst, glacial retreat, and lake infilling and drainage events. Our results fill a critical gap in the understanding of historical and potential future trajectories of change in northern high‐latitude regions.

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

Greater shrub dominance alters breeding habitat and food resources for migratory songbirds in Alaskan arctic tundra - Natalie T. Boelman; Laura Gough; John Wingfield; Scott Goetz; Ashley Asmus; Helen E. Chmura; Jesse S. Krause; Jonathan H. Perez; Shannan K. Sweet; Kevin C. Guay (Global Change Biology, 2015)
Climate warming is affecting the Arctic in multiple ways, including via increased dominance of deciduous shrubs. Although many studies have focused on how this vegetation shift is altering nutrient cycling and energy balance, few have explicitly considered effects on tundra fauna, such as the millions of migratory songbirds that breed in northern regions every year. To understand how increasing deciduous shrub dominance may alter breeding songbird habitat, we quantified vegetation and arthropod community characteristics in both graminoid and shrub dominated tundra. We combined measurements of preferred nest site characteristics for Lapland longspurs ( Calcarius lapponicus ) and Gambel's White‐crowned sparrows ( Zonotrichia leucophrys gambelii ) with modeled predictions for the distribution of plant community types in the Alaskan arctic foothills region for the year 2050. Lapland longspur nests were found in sedge‐dominated tussock tundra where shrub height does not exceed 20 cm, whereas White‐crowned sparrows nested only under shrubs between 20 cm and 1 m in height, with no preference for shrub species. Shrub canopies had higher canopy‐dwelling arthropod availability (i.e. small flies and spiders) but lower ground‐dwelling arthropod availability (i.e. large spiders and beetles). Since flies are the birds' preferred prey, increasing shrubs may result in a net enhancement in preferred prey availability. Acknowledging the coarse resolution of existing tundra vegetation models, we predict that by 2050 there will be a northward shift in current White‐crowned sparrow habitat range and a 20–60% increase in their preferred habitat extent, while Lapland longspur habitat extent will be equivalently reduced. Our findings can be used to make first approximations of future habitat change for species with similar nesting requirements. However, we contend that as exemplified by this study's findings, existing tundra modeling tools cannot yet simulate the fine‐scale habitat characteristics that are critical to accurately predicting future habitat extent for many wildlife species.

MRI-Apparent Localized Deformation of the Median Nerve Within the Carpal Tunnel During Functional Hand Loading - Jessica E. Goetz; Nicole M. Kunze; Erin K. Main; Daniel R. Thedens; Thomas E. Baer; Ericka A. Lawler; Thomas D. Brown (Annals of Biomedical Engineering, 2013)

Acinetobacter , Aeromonas and Trichococcus populations dominate the microbial community within urban sewer infrastructure - J. L. VandeWalle; G. W. Goetz; S. M. Huse; H. G. Morrison; M. L. Sogin; R. G. Hoffmann; K. Yan; S. L. McLellan (Environmental Microbiology, 2012)
Summary We evaluated the population structure and temporal dynamics of the dominant community members within sewage influent from two wastewater treatment plants (WWTPs) in Milwaukee, WI. We generated > 1.1 M bacterial pyrotag sequences from the V6 hypervariable region of 16S rRNA genes from 38 influent samples and two samples taken upstream in the sanitary sewer system. Only a small fraction of pyrotags from influent samples (∼ 15%) matched sequences from human faecal samples. The faecal components of the sewage samples included enriched pyrotag populations from Lactococcus and Enterobacteriaceae relative to their fractional representation in human faecal samples. In contrast to the large number of distinct pyrotags that represent faecal bacteria such as Lachnospiraceae and Bacteroides , only one or two unique V6 sequences represented Acinetobacter , Aeromonas and Trichococcus , which collectively account for nearly 35% of the total sewage community. Two dominant Acinetobacter V6 pyrotags (designated Acineto tag 1 and Acineto tag 2) fluctuated inversely with a seasonal pattern over a 3‐year period, suggesting two distinct Acinetobacter populations respond differently to ecological forcings in the system. A single nucleotide change in the V6 pyrotags accounted for the difference in these populations and corresponded to two phylogenetically distinct clades based on full‐length sequences. Analysis of wavelet functions, derived from a mathematical model of temporal fluctuations, demonstrated that other abundant sewer associated populations including Trichococcus and Aeromonas had temporal patterns similar to either Acineto tag 1 or Acineto tag 2. Populations with related temporal fluctuations were found to significantly correlate with the same WWTP variables (5‐day BOD, flow, ammonia, total phosphorous and suspended solids). These findings illustrate that small differences in V6 sequences can represent phylogenetically and ecologically distinct taxa. This work provides insight into microbial community composition and dynamics within the defined environment of urban sewer infrastructure.

Immunocytochemical and biochemical detection of EMMPRIN in the rat tooth germ: differentiation-dependent co-expression with MMPs and co-localization with caveolin-1 in membrane rafts of dental epithelial cells - W. Schwab; H. Harada; W. Goetz; M. Nowicki; M. Witt; M. Kasper; K. Barth (Histochemistry and Cell Biology, 2007)

Molecular analysis of two cytochrome P450 monooxygenase genes required for paxilline biosynthesis in Penicillium paxilli, and effects of paxilline intermediates on mammalian maxi-K ion channels - L. K. McMillan; R. L. Carr; C. A. Young; J. W. Astin; R. G. T. Lowe; E. J. Parker; G. B. Jameson; S. C. Finch; C. O. Miles; O. B. McManus; W. A. Schmalhofer; M. L. Garcia; et al. (Molecular Genetics and Genomics, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

An E-selectin-IgG chimera supports sialylated moiety dependent adhesion of colon carcinoma cells under fluid flow - Douglas J. Goetz; Brian K. Brandley; Daniel A. Hammer (Annals of Biomedical Engineering, 1995)